The relationship between changes in money supply and changes in share prices: The semi-strong form efficiency of the Johannesburg Stock Exchange revisited - R. D. Glass; E. V.D.M. Smit (South African Journal of Business Management, 1995)
In this article the semi-strong form of share market efficiency over the period 1978 to 1992 is considered, particularly with regard to information about changes in the money supply. To ensure a rigorous test of market efficiency, monetary growth has been decomposed, into anticipated and unanticipated elements. The All Share Index of the Johannesburg Stock Exchange is regressed against the monetary variables. The test results indicate that lagged changes in anticipated monetary growth are significant in explaining changes in share prices, a finding contrary to the efficient market hypothesis. However, the low coefficients of determination indicate that only a small percentage of the variation in share prices is explained by ex post changes in money supply and consequently the potential for a trading rule to earn superior returns to the market is limited.
Keywords: 650